(untitled) (Shahid Kirti Multidisciplinary Journal, 2026)
This paper reviews Business English courses of four-year BBS program under the Faculty of Management (FOM), Tribhuvan University (TU). These courses offer diverse contents consisting of grammar, creative texts, business vocabulary, communication message texts, research mechanics and case-analysis. They align with the objectives of FOM to produce successful future professionals, able and eligible to compete, collaborate, and contribute to operating, innovating and promoting business sectors. Development of general language skills, critical thinking skills, enriched business vocabulary, interdisciplinary knowledge and communicative competence supported by research-oriented analytical approach to problems are the basics that the courses target to attain. While the existing literature covers a wide range of fragmented issues related to Business English, the overall course assessment remains a virgin area. Hence, this article assesses the content and the collected data. Further, it examines the compatibility of FOM goals with the goals of English courses, and unravels the consistency in setting the objectives. The concepts of course design and content selection are reviewed to support the analysis. It employs a mixed approach, uses purposive sampling and the tools of semi-structured and close-ended questionnaires, and interview guidelines to collect primary data. The sample population is composed of the practitioners and students of community, private and the constituent campuses of TU, and subject committee members of English. This paper research presents its strengths and weaknesses followed by some remedial suggestions. They contribute to creating knowledge on the strengths and weaknesses of the course that benefit the diverse readers to understand it better, revise and improve accordingly as per the changing needs and context.